The Saptakoshi high dam project and its bio-physical consequences in the Arun river basin: A geographical perspective - Rai, Dil Kumar; Linkha, Tika Ram (Geographical Journal of Nepal, 2020)
The big project called Saptakoshi high dam is a bilateral project of Indian and Nepalese government under the Koshi agreement. At present, high dam issue is being the great issue especially raising by the inhabitants of upstream in Koshi basin. Therefore, this research paper attempts to examine the bio-physical consequences due to high dam in the upstream of Arun river basin. Geographic Information System (GIS) and Remote Sensing (RS) technology have been used for the spatial analysis to prepare this paper. Spatial data have been taken from topographical map and Digital Elevation Model (DEM) and the attribute data have taken from Central Bureau of Statistics (CBS), Kathmandu. It revealed that approximately 11777 hectors arable plain land will be inundated in Arun river basin only by water with river deposits due to high dam if the high dam will be built at the proposed place and proposed dam height. The proposed place lies 1.6 km upstream from Barahakshetra temple of Sunsari district and the dam height will 269 meters. Similarly, more than 10000 population might be displaced in future. There is a strong sense of fear and sadness among the people of affected communities. Till now, they have unknown about the clear information about high dam. As a result, they are sometimes demonstrating against Saptakoshi high dam. So, government should inform and ensure the alternative management of the concerned people in the initial stage to manage the future disputes.